The exploration of a CuNb3O8 Li+-storage anode compound. (3rd July 2022) - Huang, Cihui; Li, Renjie; Luo, Lijie; Chen, Yongjun; Lin, Chunfu
ABSTRACT: Niobates are regarded as prospective Li + -storage anode candidates due to the rich chemistry of niobium and crystal-structural openness. However, the exploration of niobates is still insufficient. In this study, we explore CuNb3 O8 with a large theoretical capacity is 341.9 mAh g –1 as a high-performance anode compound. The reversible redox reaction among Nb 5+, Nb 4+ and Nb 3+ during lithiation/delithiation is confirmed by ex-situ XPS, and a large reversible capacity of 231.8 mAh g –1 and safe lithiation potential of 1.53 V are achieved at 0.1 C. An intercalation-type Li + -storage mechanism is confirmed by in-situ XRD after the first lithiation process, guaranteeing the good cyclability from the second discharge–charge cycles. The Li + diffusivity in CuNb3 O8 is systematically and carefully studied. The galvanostatic intermittent titration technique tests show large Li + diffusion coefficients of 1.2 × 10 –12 /1.5 × 10 –12 cm 2 s –1 during lithiation/delithiation, and the corresponding values obtained through the cyclic voltammetry technique are similar (2.2 × 10 –12 /3.0 × 10 –12 cm 2 s –1 ). Additionally, CuNb3 O8 is successfully coupled with LiFePO4, and the resultant CuNb3 O8 //LiFePO4 full cell also exhibits good electrochemical properties, demonstrating the practicability of CuNb3 O8 for large-scale energy-storage applications.